TAX BENEFITS ANALYSIS OF TAXATION OF INDIVIDUAL ENTREPRENEURS AND SELF-EMPLOYED PERSONS (Proceedings of International Educators Conference, 2024)
The article describes individual entrepreneurs and self-employed individuals. Procedural and practical recommendations were offered to increase the importance of taxation of individual incomes in the formation of budget revenues. In addition, a study was conducted on the current state of taxation of individual entrepreneurs and self-employed persons, studies of economists were studied within the scope of the topic, and conclusions and proposals were formed.